2012
DOI: 10.1371/journal.pone.0036752
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking Accelerated Brain Aging and Induced Pre-Alzheimer-Like Neuropathology in Rats

Abstract: Cigarette smoking has been proposed as a major risk factor for aging-related pathological changes and Alzheimer's disease (AD). To date, little is known for how smoking can predispose our brains to dementia or cognitive impairment. This study aimed to investigate the cigarette smoke-induced pathological changes in brains. Male Sprague-Dawley (SD) rats were exposed to either sham air or 4% cigarette smoke 1 hour per day for 8 weeks in a ventilated smoking chamber to mimic the situation of chronic passive smokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(69 citation statements)
references
References 56 publications
(66 reference statements)
3
65
0
1
Order By: Relevance
“…For example, Ho et al (2012) found that chronic smoking predisposed the brain to Alzheimer’s disease by increasing amyloid precursor protein processing, leading to greater production and accumulation of beta amyloid protein in the hippocampus (Ho et al, 2012). Amos-Kroohs et al (2013) showed that mice exposed to cigarette smoke throughout gestation and lactation had longer latencies and impaired learning on the Morris water maze task (Amos-Kroohs et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ho et al (2012) found that chronic smoking predisposed the brain to Alzheimer’s disease by increasing amyloid precursor protein processing, leading to greater production and accumulation of beta amyloid protein in the hippocampus (Ho et al, 2012). Amos-Kroohs et al (2013) showed that mice exposed to cigarette smoke throughout gestation and lactation had longer latencies and impaired learning on the Morris water maze task (Amos-Kroohs et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…While cardiac dysfunction may have an impact on the brain, differences in risk factor profile may also be important: more smoking and less hypertension and AF were seen in ACS patients compared to TIA and stroke patients. Smoking is a risk factor for memory impairment and Alzheimer's disease more than vascular cognitive impairment,28 29 whereas hypertension and AF are associated with stroke, small vessel disease, and vascular dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Rueff-Barroso et al, 174 reported that mice exposed to daily cigarette smoke for 15 weeks demonstrated significant OxS in homogenized whole brain tissue as indicated by elevated malondialdehyde level, a marker of lipid peroxidation. Ho et al, 175 found that rats exposed to daily cigarette smoke for approximately 8 weeks showed significantly increased levels of 8-hydroxyguanine, a marker of oxidative damage to RNA and DNA nucleosides, in the dentate and CA3 subfields of the hippocampus. 175 Khanna et al, 147 reported rats exposed to cigarette smoke 5 days/week for 6 weeks exhibited significantly increased brain IFN-γ and TNF-α proinflammatory cytokine levels, as well as upregulation of the expression of multiple cytokine genes (e.g., TNF-α, IL1-α, IL1-β, Th17).…”
Section: Smoking-related Neuropathology: the Role Of Oxidative Stressmentioning
confidence: 99%